2017
DOI: 10.1007/s13300-017-0271-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Insulin Degludec for Hyperglycemia Management in Noncritical Hospitalized Patients with Diabetes: An Observational Study

Abstract: IntroductionTo assess the efficacy and safety of insulin degludec administered in a basal-bolus regimen according to the GesTIO protocol in noncritical hospitalized patients with T1DM and T2DM.MethodsMean blood glucose levels (BG) and their standard deviations (SD) at admission vs. discharge were compared in 52 subjects (48.1% ≥75 years) managed through a basal-bolus scheme including degludec. The percentages of patients with BG at target (140–180 mg/dl) or below at discharge and the incidence rate (and the 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…No symptomatic or severe hypoglycemic episodes occurred during the hospital stay, and there was evidence of a reduction in within-day glycemic variability (as measured by the coefficient of variation of glycemia every 6 h) [ 52 ]. Similar results were observed in an observational study of 52 non-critical patients with diabetes who received degludec as part of a basal–bolus regimen while hospitalized [ 53 ]. It is not possible to draw conclusions on the effect and safety of degludec-based regimens in hospitalized patients based on the current data available; it remains to be seen whether the outcomes described in these small observational studies will also be observed in large, randomized trials.…”
Section: Second-generation Basal Insulin Analogssupporting
confidence: 86%
“…No symptomatic or severe hypoglycemic episodes occurred during the hospital stay, and there was evidence of a reduction in within-day glycemic variability (as measured by the coefficient of variation of glycemia every 6 h) [ 52 ]. Similar results were observed in an observational study of 52 non-critical patients with diabetes who received degludec as part of a basal–bolus regimen while hospitalized [ 53 ]. It is not possible to draw conclusions on the effect and safety of degludec-based regimens in hospitalized patients based on the current data available; it remains to be seen whether the outcomes described in these small observational studies will also be observed in large, randomized trials.…”
Section: Second-generation Basal Insulin Analogssupporting
confidence: 86%
“…In a prospective observational study by Yamamoto et al, on in-patients with type 1 diabetes, CGM revealed that MAGE significantly decreased when switching from IGla to IDeg [35]. There have not been many similar reports for type 2 diabetes [38], and this is the first randomized clinical trial report, comparing the efficacy and safety of IGla and IDeg over a short term in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 90%